Two new species of Megophrys Kuhl and Van Hasselt (Amphibia: Megophryidae) from Sumatra, Indonesia - Munir, Misbahul; Nishikawa, Kanto; Hamidy, Amir; Smith, Eric N. (Zootaxa, 2021)
We evaluated the taxonomic status of the genus Megophrys in Sumatra using molecular and morphological data. Mitochondrial phylogenetic inference and morphological data revealed two undescribed species, one in southern Sumatra—M. selatanensis sp. nov. and one in northern Sumatra—M. acehensis sp. nov. We also detected a potential cryptic species within M. parallela, but refrain from describing this lineage here due to insufficient data. Genetic variation within Sumatran Megophrys is highly structured and will require additional geographic sampling to understand the interplay between geography and genetics in Sumatran Megophrys.